Nostalgia for Personal Past among Orphans Who Have Lost One Parent - Althahabi, Husham; Alsabab , Azhar (Al-Adab Journal, 2025)
Nostalgia for the personal past refers to an emotional psychological feeling that embodies a person’s desire to relive or reflect upon past moments and events in their life, often associated with times of happiness, safety, or emotional stability. For orphans, nostalgia for the personal past represents a profound emotional experience, combining longing for those moments with feelings of loss or sadness because they no longer exist in the present due to the death of one parent. This idealized recollection of the past, even if it includes negative aspects, focuses on the beautiful times, feelings of warmth, emotional comfort, and the desire to return to one’s personal past. From this perspective, the research problem and its significance emerged. The current research aims to: Identify the level of nostalgia for the personal past among orphans who have lost one parent. Examine the significance of differences in nostalgia for the personal past based on gender (male vs. female). The research population consisted of orphans residing in government-run orphanages under social care. A sample was selected of 240 male and female orphans aged 11 years, who had lost one parent. A scale was developed to measure nostalgia for the personal past based on Davis’s (1979) Social Identity Theory. The scale comprised 47 items distributed across six domains Reconciliatory Nostalgia Positive Nostalgia Negative Nostalgia Reflective Nostalgia Reciprocal Nostalgia Healthy Nostalgia The response options included a three-point Likert scale: Always applies to me (3 points) Sometimes applies to me (2 points) Does not apply to me (1 point) For positive items, the scoring followed this order, while for negative items, the scoring was reversed. After applying the scale, the results indicated that orphans exhibited a high level of nostalgia for the personal past, with no significant differences between males and females in their level of nostalgia. In light of the results, the researchers provided a set of recommendations and proposals.